Design of an On-Chip Tracking ADC - Mohan, Manju; Seenu, N; R Nair, Shyam; Vignesh, U P (International Journal of Engineering and Technology, 2018)
Data acquisition and conversion systems require analog signals to be converted into a digital form that can be used for further analysis. The analog signals are mostly output of sensors and transducers which transform the real-world signals into electrical signals. These electrical signals are modified to digital form by using Analog to Digital Converters (ADC). This conversion involves sampling followed by a quantizationÂ of the input signal thus will be converted to digital signal. The bandwidth of the ADC is restricted by the sampling rate and the quantization error should be kept as low as possible for better accuracy. This paper emphasis on the On-Chip design of a 12-bit Tracking ADC using PSoC which is highly reliable for digitizing the slowly varying signals. Complication encumbered in the logic that connects comparator and counter is replaced by using dual comparators, and an XOR gate. The proposed design has immense leverage in providing stable and constant data for instantaneous signal value. The major involvement is shown in making the design very simple, by efficiently using the available components, thus providing much accurate and stable digital data for further processing the slowly varying signal.Â Â